2018
DOI: 10.1016/j.jtcvs.2018.01.104
|View full text |Cite
|
Sign up to set email alerts
|

Institution of localized high-frequency electrical stimulation targeting early myocardial infarction: Effects on left ventricle function and geometry

Abstract: The unique findings from this study are 2-fold. First, targeting the MI region following the resolution of the acute event using a localized stimulation approach is feasible. Second, localized stimulation modified a key parameter of adverse post-MI remodeling (dilation) and progression to heart failure. These findings demonstrate that the MI region itself is a modifiable tissue and responsive to localized electrical stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The stimulation started 7 days after AMI and was continued for at least 21 days. This resulted in significant differences in increase of EDV (32% vs. 12%) and pulmonary capillary wedge pressure (PCWP) (+62% vs. −17%) in the untreated and treated cohorts, respectively ( n = 11) [ 87 ]. The authors reported no difference in scar size between the groups.…”
Section: Cell-free Cardiac Regeneration Therapiesmentioning
confidence: 99%
“…The stimulation started 7 days after AMI and was continued for at least 21 days. This resulted in significant differences in increase of EDV (32% vs. 12%) and pulmonary capillary wedge pressure (PCWP) (+62% vs. −17%) in the untreated and treated cohorts, respectively ( n = 11) [ 87 ]. The authors reported no difference in scar size between the groups.…”
Section: Cell-free Cardiac Regeneration Therapiesmentioning
confidence: 99%
“…Wouldn't it be great to discover a simple intervention that could be used a full week after MI that attenuates myocardial damage? In this issue of the Journal, Spinale and associates 1 present data indicating that this may be clinically possible.…”
mentioning
confidence: 93%